PENTINGKAH PENERAPAN AUDIT OPERASIONAL DIVISI PENJUALAN PADA PT. CRYSTALINDO PERSADA - Aisyah Mawar Sari; Lilik Pirmaningsih (Bussman Journal : Indonesian Journal of Business and Management, 2021)
This study aims to implement operational audits in the sales division of PT. CRYSTALINDO PERSADA provides positive benefits to increase efficiency and effectiveness as expected, this research is a case study, research method is descriptive qualitative by using primary data and secondary data, obtained based on the questionnaire, observation, questions and answers, and documentatation. With stages including determining audit objectives, audit planning (audit program), audit implementation, the results obtained are several findings, including 1) there are sales orders that canceled but are not declared canceled, 2) payments are not made by bank transfer, and 3) delay in delivery of goods to customers. It is hoped that these findings will provide recommendations to the company to be followed up so that it can improve efficiency and effectiveness in the sales division